A biomimetic nanozyme/camptothecin hybrid system for synergistically enhanced radiotherapy. Issue 24 (26th May 2020) - Zhu, Daoming; Lyu, Meng; Jiang, Wei; Suo, Meng; Huang, Qinqin; Li, Kaiyang
Abstract : Although radiotherapy (RT) has been an effective therapeutic regimen for regulating most solid tumors, its effect is limited by the hypoxic tumor microenvironment and radio-tolerance of tumor cells to a large extent. Abstract : Although radiotherapy (RT) has been an effective therapeutic regimen against most solid tumors, its effect is limited by the hypoxic tumor microenvironment and radio-tolerance of tumor cells to a large extent. Here we have designed a biomimetic nanozyme/camptothecin hybrid system for synergistically enhanced radiotherapy, which consists of an internal camptothecin (CPT)-loaded hollow MnO2 core and an external tumor cell membrane. The tumor cell membrane endows the system with excellent tumor targeting ability. The hollow MnO2 core can deliver the hydrophobic drug CPT and catalyze the production of oxygen from hydrogen peroxide in tumor tissues, which was finally degraded into Mn 2+, a T 1 -weighted contrast agent. The anti-tumor mechanism of this system includes two aspects: (i) the generated oxygen can improve the hypoxic state of the tumor microenvironment and enhance the radiotherapy sensitivity and (ii) CPT can induce cell cycle arrest in the S-phase at a low dose, which further increases the radio-sensitivity of tumor cells and augmented radiation-induced tumor damage. The results of in vivo experiments showed that the biomimetic nanozyme drug delivery system improved the hypoxic microenvironment of the tumor tissue with a high tumor inhibition rate in a murine model. This platform achieved synergistic radiotherapy sensitization and provided a novel idea for the design of a radiotherapy sensitization system.